Comparison between Diazepam and Midazolam as Premedicant to Reduce Anxiety in Patients underwent Elective Surgery Under General Anaesthesia - Karim, Md Enayet; Chowdhury, Arif Imtiaz; Ershad, Reza (IAHS Medical Journal, 2022)
Background: The majority of patients admitted to hospital for elective surgery experience anxiety preoperatively which can adversely influence the surgical procedure as well as the patient’s recovery. Reduction of anxiety and fear at preoperative period in patients of elective surgery is essential for surgical preparation. Benzodiazepines are the most commonly used drugs for this purpose. The purpose of the study to evaluate the comparative efficacy of Diazepam and Midazolam regarding onset, duration and degree of antianxiety, sedation and amnesia during surgery under general anaesthesia. Materials and methods: The study was carried out in series of 60 consequetive, unselected patients, aged 18-60 years, admitted for the elective surgery under General Anaesthesia, in Combined Military Hospital (CMH) Chattogram during the period September 2019 to February 2020. Patients receiving diazepam or midazolam as preoperative medication were taken. Anxiety was scored using VAS, sedation was scored by using Ramsay Sedation scale and anterograde amnesia by asking preoperative events after 24 hours. Results: While evaluating mean anxiety reduction only, mean reduction is greater in the diazepam group compared to that of midazolam. Desired sedation level was less achieved with midazolam. In the diazepam group, greater number of patients could not recall preoperative events. Conclusion: The standard administration of diazepam before procedure provides patients with a moderate reduction of periprocedural anxiety. Routinely, administration of midazolam has a limited effects on the reduction of anxiety. Additionally, premedication of midazolam is associated with a high incidence of adverse effects. Therefore, this study does not support the routine use of midazolam as premedication to reduce anxiety. IAHS Medical Journal Vol 5(1), June 2022; 65-69